Characterization of Pyricularia oryzae and Screening the Qualitative Resistance of Sarawak Rainfed Lowland Rice Landraces Against the Pathogen - NOR AIN, HUSSIN (Universiti Malaysia Sarawak (UNIMAS), 2021)
Rice blast disease caused by Pyricularia oryzae is one of the major diseases of rice in Sarawak, Malaysian Borneo. Unfortunately, the documentation and characterization of P. oryzae in Sarawak, resistance of Sarawak rainfed lowland landraces against P. oryzae and crucial information on the population genetics of P. oryzae in the Sarawak paddy fields are still lacking. This study aims to: 1) isolate and characterize rice blast fungus from infected paddy leaves collected from four divisions in Sarawak, viz, Miri, Sri Aman, Serian and Kuching, 2) screen the selected Sarawak lowland rice landraces (Bubuk, Pandan, Semanggang, Bario (Bintung), Entangor, Entaba (Lembut), Brunei, Bario Hitam, Perintah, Sebuti, Bario Putih, Sabak Hitam, Kuning, Rendah and Saga) for resistance against different isolates of P. oryzae at seedling stage and 3) analyse the genetic relatedness of P. oryzae in Sarawak with isolates from Peninsular Malaysia. Fifteen succeeded isolates were pre-identified as P. oryzae by morphological characteristics of spores, followed by verification through internal transcribed spacer (ITS) sequence. The isolates were evaluated for morphological characteristics, growth rate and sporulation rate, which were grown on six types of media, oatmeal agar (OMA), potato dextrose agar (PDA), malt extract agar (MEA), cornmeal agar (CMA), rice agar (RA) and barley agar (BA). Morphological characterization showed that the colony surface of the different isolates varied from smooth and fluffy to rough and flattened mycelia; some were with the present of concentric rings and some with aerial mycelia. There were no morphological characters that are unique to a specific location. The growth rate and sporulation rate of each isolate varied based on types of media used. In general, among the six media, four media, viz; OMA, PDA, CMA and BA were found favourable for mycelial growth and sporulation for most of the isolates. Disease test screening were done by inoculating 15 lowland rice